Analisis Psikopatologi Sindroma Depresi Pecandu Narkoba Kini Abstinen yang Mengalami Stroke - Lainatul Mudzkiyyah (Philanthropy: Journal of Psychology, 2018)
This study aimed to uncover how to analyze psychopathology in depth about drug addicts with depression syndrome after abstinence from substances and suffer a stroke. This study involved one (1) male subject, aged 22 years, drug addicts are now abstinent in drug rehabilitation treatment, experiencing depression, and stroke due to substances. This study used a qualitative approach to case studies. Data extraction in this study used observation, in-depth interviews, medical records, and psychological tests such SPM (Scale Progressive Matrick), Graphics (BAUM, DAP, HTP, WTZ), BDI II. The results of this study indicated that introverted personality types, low cognitive abilities, family neglect contributed to depression syndrome with poor prognosis. Other than that, experiencing depression was not caused by abstinence of substances but because of psychological factors.